Energy Harvesting via Natural Photo-Sensitizer based Dye-Sensitized Solar Cell using Nanostructured Photo-Electrodes (Bulletin of Pure and Applied Sciences – Physics, 2020)
In this paper, we investigated the structural, chemical and photovoltaic  characterization of commonly found natural dyes. The dyes have extracted from  plant materials like the bougainvillea, yellow bells (piliya), golden shower (amaltas),  hibiscus, peepal and mint. Based on the structure and properties of the dye, which  the fact that “like extracts like”, a suitable solvent has selected, in which the dyes  have extracted efficiently. The extracted dyes act as natural photo-sensitizers, which  has mostly used for the fabrication of dye sensitized solar cells (DSSCs). The cells  have been fabricated by using TiO2 as a semiconducting layer deposited on  transparent fluorine doped tin oxide (FTO) conducting glass plate with the help of  doctor blading method. The J-V characteristics curves of all fabricated cells were  measured by using source-meter, SMU-instrument etc and further analysed for its  better performance was investigated.